2015
DOI: 10.1128/genomea.00466-15
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of Two Clinical Isolates of Mycobacterium tuberculosis from Sputum of Kazakh Patients

Abstract: Here, we report the draft genome sequences of two clinical isolates of Mycobacterium tuberculosis (MTB-476 and MTB-489) isolated from sputum of Kazakh patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Previous studies in Kazakhstan were reported about the mutations associated with drug resistance in genes of M. tuberculosis . For example, some research work conducted in Kazakhstan was carried out investigating the mutations in genes of M. tuberculosis responsible for drug resistance to various anti-TB drugs, especially for rifampicin and isoniazid [ 17 , 18 , 19 ], molecular genotyping of M. tuberculosis [ 20 , 21 , 22 , 23 ], and whole-genome sequencing [ 24 , 25 , 26 , 27 ]. Hillemann et al [ 17 ] in their study evaluated the possible associations of specific mutations leading to resistance to rifampicin and isoniazid with isolates of the Beijing genotype and isolates of other M. tuberculosis genotypes (non-Beijing strains) from Kazakhstan in the early 2000s.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in Kazakhstan were reported about the mutations associated with drug resistance in genes of M. tuberculosis . For example, some research work conducted in Kazakhstan was carried out investigating the mutations in genes of M. tuberculosis responsible for drug resistance to various anti-TB drugs, especially for rifampicin and isoniazid [ 17 , 18 , 19 ], molecular genotyping of M. tuberculosis [ 20 , 21 , 22 , 23 ], and whole-genome sequencing [ 24 , 25 , 26 , 27 ]. Hillemann et al [ 17 ] in their study evaluated the possible associations of specific mutations leading to resistance to rifampicin and isoniazid with isolates of the Beijing genotype and isolates of other M. tuberculosis genotypes (non-Beijing strains) from Kazakhstan in the early 2000s.…”
Section: Discussionmentioning
confidence: 99%
“…Only some publications relate to preliminary data and reported several genome sequences of DR (including one XDR and several MDR) clinical isolates of M. tuberculosis isolated in Kazakhstan performed by using a next-generation sequencing platform [ 24 , 25 , 26 , 27 , 28 , 29 ]. Drafts of complete genome sequences of two Kazakhstani isolates [ 24 ] and one isolate with extensive drug resistance [ 26 , 27 ] were published by our group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies on biological diversity and identification of mutations in specific genomic regions encoding drug resistance were performed in Kazakhstan ( Kozhamkulov et al, 2011 ; Ibrayeva et al, 2014 ; Akhmetova et al, 2015 ; Skiba et al, 2015 ). Only a few publications related to whole-genome sequencing of clinical isolates performed by next-generation sequencing platforms have briefly reported draft genome sequences of Mtb strains circulating in Kazakhstan ( Ilin et al, 2015 ; Kairov et al, 2015 ; Daniyarov et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is extremely important to examine susceptible and resistant strains with different mutations in genes encoding drug metabolism among M.tuberculosis isolates. Previous investigations of M.tuberculosis isolates circulated in Kazakhstan have been performed using Sanger sequencing, spoligotyping, MIRU-VNTR typing and NGS approaches [2] , [3] , [4] . Here, we report the whole genome sequence and analysis of XDR-TB strain, performed by next-generation sequencing platform.…”
Section: Data Descriptionmentioning
confidence: 99%